Representasi Kemiskinan dalam Novel Dekat dan Nyaring Karya Sabda Armandio Alif - Azizah, Aminul (TSAQOFAH, 2026)
Although the issue of poverty in literary works has received attention in several previous studies, studies that specifically discuss the forms, causes, and impacts of poverty in the novel Dekat dan Nyaring by Sabda Armandio Alif remain limited. This study aimed to describe and analyze the representation of poverty in the novel Dekat dan Nyaring, particularly in relation to the forms of poverty, causal factors, and their impacts on the lives of the characters. This study used a qualitative approach with a descriptive method and a literary study design based on the sociology of literature. The research data consisted of words, phrases, sentences, dialogues, narratives, and events that represent poverty in the novel Dekat dan Nyaring, published by Penerbit baNANA in 2019 with a total of 110 pages. Data were collected through close reading, marking relevant parts of the text, recording quotations, and classifying data based on the categories of forms, causes, and impacts of poverty. The main research instrument was the researcher, while the supporting instruments consisted of recording sheets and data classification tables. Data were analyzed descriptively and qualitatively through the stages of identification, classification, analysis, and drawing conclusions. The results showed that the representation of poverty in the novel includes three main forms, namely absolute poverty, relative poverty, and structural poverty. The causal factors of poverty include natural and artificial factors, while its impacts are evident in legal, moral, and social aspects. This finding contributes to the development of sociology of literature studies by expanding the understanding of poverty as a multidimensional issue in contemporary Indonesian literature. Thus, the novel Dekat dan Nyaring can be read as a sociocultural document that reflects inequality, eviction, and the struggle of the urban poor, while also opening opportunities for further research on urban poverty, living space, and social injustice in Indonesian novels.